PENGARUH PRESTASI BELAJAR MATA PELAJARAN PRODUKTIF DAN EFEKTIVITAS LABORATORIUM PELATIHAN USAHA TERHADAP MINAT WIRAUSAHA SISWA - Purnami, Tri Wulaning (UNIVERSITAS NEGERI SURABAYA, 2016)
The purpose of this study is: (1) analyze the influence of the learning achievement of productive subjects of the entrepreneurial interests of students; (2) analyze the influence of the effectiveness of business training laboratory for students' entrepreneurial interest. Samples proportional random sampling 254 students of class XI Bismen of three schools namely SMK 1 Surabaya, SMKN 4 Surabaya, Surabaya SMKN 10. Methods of data collection using documentation and questionnaires. Data analysis using multiple linear regression statistical test, F test and t test, analysis using IBM SPSS Statistics 22 programs. Results of the study: (1) there is a significant positive influence learning achievement of productive subjects to the students' entrepreneurial interest; (2) there is a positive influence and insignificant effectiveness of business training laboratory for students' entrepreneurial interest; (3) there is a significant positive influence learning achievement of productive subjects and effectiveness of business training laboratory for students' entrepreneurial interest